1996
DOI: 10.1046/j.1365-2958.1996.1271487.x
|View full text |Cite
|
Sign up to set email alerts
|

Re‐examination of the role of the periplasmic domain of EnvZ in sensing of osmolarity signals in Escherichia coli

Abstract: In Escherichia coli, EnvZ senses changes in the osmotic conditions of the growth environment and controls the phosphorylated state of the regulatory protein, OmpR. OmpR-phosphate regulates the expression of the porin genes, ompF and ompC. To investigate the role of the periplasmic domain of EnvZ in sensing of osmolarity signals, portions of this domain were deleted. Cells containing the EnvZ mutant proteins were able to regulate normally the production of OmpF and OmpC in response to changes in osmolarity. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 29 publications
2
29
0
3
Order By: Relevance
“…These leucine residues reside at the N-terminal amphoteric helical region corresponding to the N-alpha domain identified in the present study. In addition, earlier deletion analysis has shown that removal of residues Met 56 -Glu 80 or Ile 81 -Arg 146 , and substitution of Met 56 -Arg 146 from EnvZ per with the non-homologous periplasmic domain of PhoR, had no effect on EnvZ function [18]. Our biophysical data indicate that EnvZ per contains a proteolytically resistant CT domain, corresponding to residues Glu 83 -Arg 162 , connected to the highly conserved N-alpha region.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…These leucine residues reside at the N-terminal amphoteric helical region corresponding to the N-alpha domain identified in the present study. In addition, earlier deletion analysis has shown that removal of residues Met 56 -Glu 80 or Ile 81 -Arg 146 , and substitution of Met 56 -Arg 146 from EnvZ per with the non-homologous periplasmic domain of PhoR, had no effect on EnvZ function [18]. Our biophysical data indicate that EnvZ per contains a proteolytically resistant CT domain, corresponding to residues Glu 83 -Arg 162 , connected to the highly conserved N-alpha region.…”
Section: Discussionmentioning
confidence: 45%
“…While in vitro studies on reconstituted E. coli EnvZ have shown a response to changes in K + concentration [17], the mechanisms underlying the sensing function have not been elucidated. Replacement of up to 91 amino acids (Met 56 -Arg 146 ) from the C-terminal region of EnvZ per with the non-homologous periplasmic domain of PhoR had no effect on the regulation of OmpF and OmpC expression [18], thus putting in question the role of EnvZ per in sensing osmolarity signal(s). More recently, however, mutagenesis studies have suggested that leucine residues in a conserved N-terminal region of the periplasmic domain (Pro 41 -Glu 53 ) may play a role in osmotic signal transduction by mediating dimerization of EnvZ per [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations and deletions of the linker region exhibit various low and high osmolarity locked phenotypes and provide evidence that this region is critical for signalling (Park & Inouye 1997). Periplasmic deletions result in a locked high osmolarity phenotype or have no effect (reviewed in Forst & Roberts 1994;Leonardo & Forst 1996). An N-terminal truncation of 38 amino acids that prevents proper localization of EnvZ, retains its ability to be autophosphorylated, but cannot respond to osmolarity changes.…”
Section: Genetic Analysismentioning
confidence: 99%
“…subtilis, chemotaxis and osmoregulation in E. coli, have been extensively studied (Forst et al, 1989;Bourret et al, 1989;Leonardo & Forst, 1996;Stephenson & Hoch, 2002). However, until recently, few studies have been conducted on their origin and evolution.…”
Section: Introductionmentioning
confidence: 99%